ESG DISCLOSURE DAN INTEGRATED REPORTING: TREN GLOBAL DAN PERSPEKTIF PASAR NEGARA BERKEMBANG - Gjosphink Putra Umar Sakka; Omasrianto Omasrianto; La Ode Safarudin; Burhanuddin Burhanuddin; Hasnita Hasnita (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
The development of sustainability reporting and ESG disclosure has become a major focus of corporate accountability at the global level. This article presents a narrative review of the literature from 2019 to 2025 on ESG reporting practices and integrated reporting (IR) in developed markets and emerging markets. The review findings indicate an increasing trend in the adoption of ESG disclosure, the development of international standards and frameworks such as GRI, SASB, IR/IIRC, TCFD, and ESRS, as well as a shift from voluntary to mandatory disclosure. The impact of ESG disclosure on firm value, cost of capital, and corporate reputation generally shows positive outcomes, although several challenges remain, including standard inconsistency, greenwashing, and reporting complexity. This study identifies research gaps related to the use of artificial intelligence for ESG analysis, digital tools, and ESG implementation in emerging markets. The article provides practical implications for companies and regulators, as well as directions for future research in sustainability accounting. ABSTRAK Perkembangan sustainability reporting dan ESG disclosure telah menjadi fokus utama akuntabilitas perusahaan global. Artikel ini menyajikan tinjauan naratif terhadap literatur tahun 2019–2025 mengenai praktik pelaporan ESG dan integrated reporting (IR) di pasar maju dan emerging markets. Hasil tinjauan menunjukkan tren peningkatan penerapan ESG disclosure, perkembangan standar dan framework internasional (GRI, SASB, IR/IIRC, TCFD, ESRS), serta pergeseran dari voluntary ke mandatory disclosure. Dampak ESG disclosure terhadap nilai perusahaan, biaya modal, dan reputasi menunjukkan hasil positif, meskipun terdapat tantangan berupa inkonsistensi standar, greenwashing, dan kompleksitas pelaporan. Studi ini mengidentifikasi gap penelitian terkait penggunaan AI untuk analisis ESG, digital tools, dan penerapan di emerging markets. Artikel ini memberikan implikasi praktis bagi perusahaan dan regulator, serta arah penelitian lebih lanjut dalam akuntansi keberlanjutan.